First detection of Echinococcus multilocularis in dogs in a highly endemic area of Poland - Karamon, Jacek; Samorek-Pieróg, Małgorzata; Kochanowski, Maciej; Dąbrowska, Joanna; Sroka, Jacek; Gołąb, Elżbieta; Umhang, Gérald; Cencek, Tomasz (Folia Parasitologica)
The aim of the investigation was to estimate the epizootic situation concerning infection by the cestode Echinococcus multilocularis Leuckart, 1863 in dogs (Canis lupus familiaris Linnaeus) from a Polish region where this parasite is highly prevalent in red foxes. Faecal samples (n = 148) were collected from rural dogs in Podkarpackie Province. Samples were examined through nested PCR (for E. multilocularis), multiplex PCR (E. multilocularis, species of Taenia Linnaeus, 1758) and PCR [E. granulosus (Batsch, 1786)]. Specific products were sequenced. Faeces were also examined coproscopically. In samples from two dogs (1.4%), there were positive PCR results for E. multilocularis. Taenia-specific PCR products were found in nine dogs (6.1%). Sequencing identified Taenia serialis (Gervais, 1847), T. hydatigena Pallas, 1766, T. pisiformis (Bloch, 1780) and Hydatigera taeniaeformis (Batsch, 1786). One sample (0.7%) was identified as Mesocestoides litteratus (Batsch, 1786). All samples were negative for E. granulosus with PCR. Taking into account coproscopic and PCR results, 28% of dogs were infected with helminths (8% with tapeworms). It should be stressed that one of the infected with E. multilocularis dogs shed eggs of the Taenia type and had a habit of preying on rodents. This investigation revealed the presence of E. multilocularis in dogs for the first time in Poland. Jacek Karamon, Małgorzata Samorek-Pieróg, Maciej Kochanowski, Joanna Dąbrowska, Jacek Sroka, Elżbieta Gołąb, Gérald Umhang, Tomasz Cencek. Obsahuje bibliografii